Effect of Combined Electromagnetic Field and Plantar Flexion Resistance Exercise on Wound Healing in Patients with Venous Leg Ulcers: A Randomized Controlled Trial - Heba Mohamed Mohamady; Mona Mohamed Taha; Yasser M. Aneis; Monira I. Aldhahi; Asmaa Fawzy Attalla (Medicina, 2023)
Background and Objectives: Venous ulcers are recognized to be more painful and resistant to therapy than ulcers of other etiologies. Various methods have been used for the conservative treatment of venous ulcers, such as pulsed electromagnetic field (PEMF) and plantar exercise, which promote wound healing due to a range of physiological effects. The study aimed to examine the effect of combined pulsed electromagnetic field therapy and plantar flexion resistance exercise (PRE) on patients with venous leg ulcers (VLUs). Materials and Methods: The study was a prospective, randomized controlled trial. A total of 60 patients between the ages of 40 and 55 with venous ulcers were randomly assigned to 1 of 3 groups. For up to 12 weeks, the first group received PEMF therapy and plantar flexion resistance exercise (PRE) therapy in addition to conservative ulcer treatment for up to 12 weeks. The second group received only PEMF therapy in addition to conservative ulcer treatment, while the third group served as the control and received only conservative ulcer treatment. Results: At the four-week follow-up, the two experimental groups revealed a considerable variation in ulcer surface area (USA) and ulcer volume (UV), with no significant change in the control group. At the 12-week follow-up, there were significant differences between the three groups, while group A underwent the most significant changes, with mean differences at [95% confidence interval] of (−4.75, −3.82, −0.98) for USA and (−12.63, −9.55, −2.45) for UV, respectively. Conclusions: On a short-term basis, adding a plantar resistance exercise to the PEMF had no appreciable short-term effects on ulcer healing; however, their combination had more pronounced medium-term effects.